Designing and Developing Audiobooks That Suit the Needs of Tenth-Grade, Second-Semester Visually Impaired Students at SLB N 1 Tabanan - Jayani, Ni Wayan Septia; Kusuma, I Putu Indra; Pratiwi, Ni Putu Astiti; Ana, I Ketut Trika Adi (Lexeme : Journal of Linguistics and Applied Linguistics, 2026)
This study addresses the limited availability of structured and accessible English learning materials for students with visual impairments (VIS), particularly in the Indonesian inclusive education context. The study focuses on designing and developing English audiobooks that suit the learning needs of tenth grade second semester visually impaired students at SLB Negeri 1 Tabanan. The objective of the study was to design and develop audiobooks that suit the needs of visually impaired students (VIS) in learning English. Employing a qualitative research design, the study adopted the Successive Approximation Model (SAM), involving iterative stages of project planning, design, prototyping, expert evaluation, and revision. Data were collected through classroom observation, interviews, reflective journaling, and expert judgment. The findings indicate that the developed audiobooks successfully enhanced material clarity, accessibility, and learner engagement, featuring bilingual vocabulary support, clear narration, consistent unit structure, pronunciation modeling, and simplified listening tasks. Expert validation confirmed the suitability of the content for visually impaired learners. In conclusion, the study demonstrates that well-designed audiobooks can function as core instructional media that promote independent learning and inclusive EFL instruction. Thus, teachers can integrate the audiobooks into daily instruction to supplement limited teaching resources, while students can use them for repeated practice beyond the classroom.